An Overview of CubeSat Missions and Applications - Konstantinos-Panagiotis Bouzoukis; Georgios Moraitis; Vassilis Kostopoulos; Vaios Lappas (Aerospace, 2025)
The proliferation of CubeSats in Earth orbit has accelerated dramatically in recent years, with projections indicating continued growth in the coming decades. This review examines the evolution of CubeSat applications, from basic technology demonstrations to complex mission capabilities, including Earth observation, telecommunications, astronomical research, biological experimentation, and deep-space exploration. A notable shift has occurred over the past fifteen years, with CubeSats transitioning from standalone platforms to integrated nodes within larger constellations, particularly for Earth observation and telecommunications applications. We analyze the key enabling factors behind the CubeSat revolution, including decreased launch costs, miniaturized electronics, standardized components, and institutional support frameworks. Through the examination of significant past, current, and planned missions, this paper provides a comprehensive overview of CubeSat capabilities across diverse application domains. The review highlights how these miniaturized satellite platforms are democratizing access to space while enabling innovative scientific and commercial applications previously restricted to larger spacecraft.